2008
DOI: 10.1007/s00284-008-9103-2
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Resistance to Antibiotics, UV-B, and Arsenic in Bacteria Isolated from Extreme Environments in High-Altitude (Above 4400 m) Andean Wetlands

Abstract: High-altitude Andean wetlands are pristine environments with extreme conditions such as high UV radiation, high heavy metal content (mainly arsenic), high salinity, and oligotrophy. In this paper, the UV-B resistance and tolerance to arsenic of phylogenetically characterized bacteria (Actinobacteria [six isolates], Firmicutes [four isolates], and gamma-Proteobacteria [three isolates]) isolated from Laguna Vilama (4400-m altitude) and Laguna Azul (4560 m) were determined. In addition, given that multiple antibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
105
0
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(119 citation statements)
references
References 22 publications
9
105
0
5
Order By: Relevance
“…Some studies demonstrated that microorganisms from extreme environments with multiple heavy metal resistances, namely, arsenate and antimonite, are also resistant to antibiotics that, surprisingly, are not found in the environment from which the organisms originated (15,16). Resistances are commonly coupled in genetic elements that, despite being common on plasmids, can occur also in the chromosomes (17,18).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies demonstrated that microorganisms from extreme environments with multiple heavy metal resistances, namely, arsenate and antimonite, are also resistant to antibiotics that, surprisingly, are not found in the environment from which the organisms originated (15,16). Resistances are commonly coupled in genetic elements that, despite being common on plasmids, can occur also in the chromosomes (17,18).…”
mentioning
confidence: 99%
“…In order to create a collection of aerobic heterotrophic bacterial strains from the Lucky Strike vent site, aliquots from sediment samples were inoculated in Reasoner's 2A (R2A) agar (Oxoid, Thermo Scientific, United Kingdom) containing (amounts in grams/liter are given in parentheses) yeast extract (0.5), proteose peptone (0.5), casein hydrolysate (0.5), glucose (0.5), starch (0.5), sodium pyruvate (0.3), di-potassium hydrogen phosphate (0.3), magnesium sulfate anhydrous (0.024), and agar-agar (15), and prepared with seawater filtrate (SWF) collected from coastal seawater. Each dilution was incubated at 15°C for up to 1 month.…”
mentioning
confidence: 99%
“…The 16S rRNA gene library revealed that the Acidobacteria which could cumulate heavy metals occupied 60% of bacteria in the plant rhizosphere microbial communities and the other bacteria were Firmicutes, CFB (Gremion et al, 2003). A lot of Firmicutes bacteria could produce endospores, which could resist dehydration and survive in extreme conditions (Dib et al, 2008). In this paper, the CB01, CB02 and CB03 in the DGGE were detected to be Bacilli of Firmicutes.…”
Section: Discussionmentioning
confidence: 84%
“…Mutation of fungi for making them metal resistant are usually done by chemical applications [23][24]. Some groups have worked on use of UV radiation to induce metal resistance in bacteria [25][26].It is already reported that exposure to gamma showed maximum potential to induce mutation in fungi (Metarhizium anisopliae) than that of UV or other chemical mutagens [14].Gamma exposed fungal strain improvement for different industrial as well as ecological purposes are also reported earliar [27][28]. Thus our study showed that possibility of utilising gamma irradiation for increasing Cd removal efficiency of fungi.…”
Section: Resultsmentioning
confidence: 99%